2014
DOI: 10.3109/00952990.2014.925467
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline in addictive disorders: a review of the literature

Abstract: Background Citicoline is a dietary supplement that has been used as a neuroprotective agent for neurological disorders such as stroke and dementia. Citicoline influences acetylcholine, dopamine, and glutamate neurotransmitter systems; serves as an intermediate in phospholipid metabolism; and enhances the integrity of neuronal membranes. Interest has grown in citicoline as a treatment for addiction since it may have beneficial effects on craving, withdrawal symptoms, and cognitive functioning, as well as the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…Previous research has not been conducted to determine whether citicoline could have an effect on cocaine urine drug screen sensitivity. Although this possibility cannot be entirely ruled out, citicoline is not structurally similar to cocaine or other substances of abuse and has no known drug-drug or other interactions (22). The use of CBT as a psychosocial platform potentially had advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has not been conducted to determine whether citicoline could have an effect on cocaine urine drug screen sensitivity. Although this possibility cannot be entirely ruled out, citicoline is not structurally similar to cocaine or other substances of abuse and has no known drug-drug or other interactions (22). The use of CBT as a psychosocial platform potentially had advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Citicoline is sold as a prescription drug in Japan and Europe and over the counter as a dietary supplement in the United States (22). Citicoline has a mild side effect profile, and a Cochrane review observed that citicoline "tended to be associated with fewer adverse effects than placebo" in elderly patients with cognitive disorders (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely demonstrated that citicoline can activate the biosynthesis of phospholipids in neuronal membranes and can stimulate cerebral metabolism and some brain neurotransmitter systems, including the dopaminergic system. 22 When used as a long-term medication, it is a safe and well-tolerated drug that has no significant systemic side effects, and it has been used in the pharmacotherapy of senile cognitive impairment, 23 addictive disorders, 24 stroke, head trauma and Parkinson's disease 25 as well as in amblyopia 26 and glaucoma. 27,28 At present, citicoline is available in the United States as a dietary supplement for neurological disorders such as stroke and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Cytidine‐50‐diphosphocholine or CDP‐choline with the generic name of citicoline is a widely consumed dietary supplement (Wignall & Brown, ) which is hydrolyzed into choline and cytidine (a component of RNA) in the intestine (Wurtman, Regan, Ulus, & Yu, ). It is a middle product and precursor in the synthesis of cell membrane phospholipids and the neurotransmitter acetylcholine (Grieb, ; Tayebati & Amenta, ).…”
Section: Introductionmentioning
confidence: 99%